KAPASITAS ANTIOKSIDAN DAN ANTIBAKTERI LOLOH SEMBUNG (Blumea balsamifera) BERDASARKAN METODE EKSTRAKSI - IGA. Wita Kusumawati; IBA. Yogeswara (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Loloh sembung (Blumea balsamifera) is a traditional herbal drink which of the extraction methods can be done by boiling and brewing. Loloh sembung was prepared from fresh and dried leaves. Loloh sembung extracted by different methods producing phenolic content, tannin content, antioxidant capacity, are different. Dried leaves were extracted by brewing have high content of total phenolic was at 13.15±0.11 mg GAE/g sample, while dried leaves were extracted by boiling have high content of tannin and antioxidant capacity were at 1.65±0.01 mg TAE/g sample and 5.55±0.01 mg GAE/g sample respectiveliy. Both of fresh and dried leaves were extracted by boiling and brewing were not show inhibition against Escherichia coli and Staphylococcus aureus bacteria.